2015
DOI: 10.1371/journal.pone.0145915
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for the Role of the Vacuole in Supplying Secretory Organelles with Ca2+ in Hansenula polymorpha

Abstract: Processes taking place in the secretory organelles require Ca2+ and Mn2+, which in yeast are supplied by the Pmr1 ion pump. Here we observed that in the yeast Hansenula polymorpha Ca2+ deficiency in the secretory pathway caused by Pmr1 inactivation is exacerbated by (i) the ret1-27 mutation affecting COPI-mediated vesicular transport, (ii) inactivation of the vacuolar Ca2+ ATPase Pmc1 and (iii) inactivation of Vps35, which is a component of the retromer complex responsible for protein transport between the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In contrast, alternating results regarding protein secretion were obtained in H. polymorpha, P. pastoris and Y. lipolytica disrupted for PMR1, which might be partly attributed to a reduced viability of the strains thus eventually masking the positive effects on secretion [112][113][114][115]. Furthermore, it was recently demonstrated that there are also Pmr1-independent routes of Ca 2+ delivery to the secretory organelles operating in H. polymorpha [116].…”
Section: Targeted Induction Of the Hsr By Overexpression Of Its Const...mentioning
confidence: 96%
“…In contrast, alternating results regarding protein secretion were obtained in H. polymorpha, P. pastoris and Y. lipolytica disrupted for PMR1, which might be partly attributed to a reduced viability of the strains thus eventually masking the positive effects on secretion [112][113][114][115]. Furthermore, it was recently demonstrated that there are also Pmr1-independent routes of Ca 2+ delivery to the secretory organelles operating in H. polymorpha [116].…”
Section: Targeted Induction Of the Hsr By Overexpression Of Its Const...mentioning
confidence: 96%
“…Two of these function in endosomal compartments: the vacuolar protein sorting 35 (VPS35), which is important for vesicular transport from the endosomes to the Golgi, and the vacuolar protein sorting 13 (VPS13C), which is important for vesicular transport from the Golgi to the endosomes. These proteins affect Ca 2+ influx in the secretory pathway and protein recycling ( Table 1 ) ( Fokina et al, 2015 ; Mehta et al, 2016 ; Wang et al, 2016 ). The third is a lysosomal protein, LRRK2, that is linked through an unknown mechanism to the regulation of Ca 2+ homeostasis in this organelle ( Table 1 ) ( Funayama et al, 2002 ; Gómez-Suaga et al, 2012 ; Gómez-Suaga and Hilfiker, 2012 ; Hockey et al, 2015 ).…”
Section: Intracellular Ca 2+ Stores and Their Derementioning
confidence: 99%
“…This has led to emergence of an additional model organism in Michael's lab, namely methylotrophic yeast Hansenula polymorpha. Using Hansenula, it was shown that a defect of the retrograde vesicular transport between the secretory organelles affects calcium homeostasis, probably due to the disruption of calcium delivery from the vacuole to the endoplasmic reticulum [31,32]. Michael's team has also shown that, unlike S. cerevisiae, H. polymorpha lacking both Golgi apparatus Ca 2+ /Mn 2+ ATPase Pmr1 and vacuolar Ca 2+ ATPase Pmc1, dies not due to excess of Ca 2+ in the cytosol but due to Ca 2+ shortage in the secretory pathway [32].…”
mentioning
confidence: 99%
“…Using Hansenula, it was shown that a defect of the retrograde vesicular transport between the secretory organelles affects calcium homeostasis, probably due to the disruption of calcium delivery from the vacuole to the endoplasmic reticulum [31,32]. Michael's team has also shown that, unlike S. cerevisiae, H. polymorpha lacking both Golgi apparatus Ca 2+ /Mn 2+ ATPase Pmr1 and vacuolar Ca 2+ ATPase Pmc1, dies not due to excess of Ca 2+ in the cytosol but due to Ca 2+ shortage in the secretory pathway [32]. The most recent study by Michael's lab, involving H. polymorpha as a model organism revealed a link between protein glycosylation and phosphate transport [33].…”
mentioning
confidence: 99%